2016
DOI: 10.1128/aac.00301-16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoroquinolones and Macrolides on Eradication and Resistance of Haemophilus influenzae in Chronic Obstructive Pulmonary Disease

Abstract: Little is known about the effect of antibiotics on eradication of carriage and development of resistance in Haemophilus influenzae in individuals with chronic obstructive pulmonary disease (COPD). Our goals were to assess antibiotic susceptibilities, prevalence of resistance genes, and development of resistance in H. influenzae and to evaluate the effect of macrolide and fluoroquinolone administration on H. influenzae eradication. Data were from a 15-year longitudinal study of COPD. Genome sequence data were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
2
26
0
1
Order By: Relevance
“…186 A 15-year longitudinal study conducted by Pettigrew et al concluded that fluoroquinolones represent the best choice for eradicating H. influenzae in COPD patients. 184 In their study, none of the bacterial isolates developed resistance to fluoroquinolones. 184 Even though P. aeruginosa is a relatively uncommon cause of COPD exacerbations, its incidence is on the rise and the rapid emergence and spread of MDR (defined by resistance to at least three antibiotic classes) is a serious cause for concern.…”
Section: Emerging Antimicrobial Resistance In Copd: Implications For mentioning
confidence: 96%
See 2 more Smart Citations
“…186 A 15-year longitudinal study conducted by Pettigrew et al concluded that fluoroquinolones represent the best choice for eradicating H. influenzae in COPD patients. 184 In their study, none of the bacterial isolates developed resistance to fluoroquinolones. 184 Even though P. aeruginosa is a relatively uncommon cause of COPD exacerbations, its incidence is on the rise and the rapid emergence and spread of MDR (defined by resistance to at least three antibiotic classes) is a serious cause for concern.…”
Section: Emerging Antimicrobial Resistance In Copd: Implications For mentioning
confidence: 96%
“…184 In their study, none of the bacterial isolates developed resistance to fluoroquinolones. 184 Even though P. aeruginosa is a relatively uncommon cause of COPD exacerbations, its incidence is on the rise and the rapid emergence and spread of MDR (defined by resistance to at least three antibiotic classes) is a serious cause for concern. A comparative study conducted in Spain has demonstrated that the carriage of MDR P. aeruginosa in COPD patients was associated with increased mortality rates and more recent work in AECOPD reveals a high burden of antibiotic resistance.…”
Section: Emerging Antimicrobial Resistance In Copd: Implications For mentioning
confidence: 96%
See 1 more Smart Citation
“…The development of azithromycin resistance in H. influenzae presents a major public health challenge. In order to understand the factors driving NTHi resistance to azithro-mycin, we investigated isolates from a 20-year longitudinal study of COPD infection conducted in Buffalo, NY, a unique collection of NTHi sputum isolates with corresponding whole-genome sequences and epidemiologic, clinical, and antibiotic susceptibility data (4,13). From this unique collection, serially obtained NTHi isolates which persisted in COPD patients during treatment with azithromycin were further analyzed for resistance to or elevated MICs of azithromycin.…”
mentioning
confidence: 99%
“…From this unique collection, serially obtained NTHi isolates which persisted in COPD patients during treatment with azithromycin were further analyzed for resistance to or elevated MICs of azithromycin. Two strains developed a known macrolide resistance mutation in L22 during persistence in the human airways; in this protein, a switch from glycine to aspartic acid at amino acid 91 (G91D) occurred (13). Thus, the objectives of this study were to (i) compare azithromycin pharmacodynamics (PD) in vitro in the "first" and "last" isolates of two persistent strains of NTHi from COPD patients who received azithromycin and (ii) simulate the human pharmacokinetic (PK) profiles of azithromycin Z-Pak dosing regimens in the hollow-fiber infection model (HFIM) against the strains upon acquisition by the patients to understand the profile and time course of bacterial response and understand the evolution of resistance.…”
mentioning
confidence: 99%